2021
DOI: 10.37034/jsisfotek.v3i4.195
|View full text |Cite
|
Sign up to set email alerts
|

Sistem Pakar dalam Membandingkan Metode Forward Chaining dengan Certainty Factor untuk Mengidentifikasi Jenis Kulit Wajah

Abstract: Kulit merupakan salah satu bagian tubuh yang memiliki sifat fleksibel untuk melindungi tubuh manusia dari dampak ekologis. Sebagian besar orang membutuhkan kulit wajah yang kencang dan terbebas dari penyakit kulit, terutama kulit berjerawat. Oleh karena itu, setiap orang harus melakukan perawatan wajah dan menggunakan beberapa bahan yang cocok untuk kulit wajah, ada lima jenis kulit normal, kulit berminyak, kulit kuring, kulit kombinasi dan kulit sensitif. Untuk mengkaji jenis kulit wajah dengan membandingkan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…An expert system is a computer-based system that takes events, reasoning and human knowledge so as to be able to solve existing problems as done by scientists or an expert in their field. In the 1970s, expert systems first appeared and were discovered by artificial intelligence scientists so that in the 1980s they were generally defined [3], [14], [15]. Expert systems are made based on existing rules in solving problems or making diagnoses.…”
Section: Expert Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…An expert system is a computer-based system that takes events, reasoning and human knowledge so as to be able to solve existing problems as done by scientists or an expert in their field. In the 1970s, expert systems first appeared and were discovered by artificial intelligence scientists so that in the 1980s they were generally defined [3], [14], [15]. Expert systems are made based on existing rules in solving problems or making diagnoses.…”
Section: Expert Systemmentioning
confidence: 99%
“…Therefore, it can be concluded that the basic conclusion of the Certainty Factor formula is the rule if Evidence (E) then appears the result of the Hypothesis (H) using equation (2). If all the values of E have known the certainty value, the equation can be changed as shown in equation (3).…”
Section: Cf(he) = Mb(he) -Md(he)mentioning
confidence: 99%
See 3 more Smart Citations